Makna Simbol Dewi Saraswati pada Fungsi Perpustakaan - Masriastri, I Gusti Ayu Ketut Yuni (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The library is chosen to be one of the institutions as agents of change. The digital era library acts as an agent of change, agent of culture, center for the development of science and technology as well as being a place for educational recreation. The library is now also a place for the transfer of knowledge. It is said so because the library is a place that stores various information needed by the community and a library is a place for the creation of intellectual embryos. Dewi Saraswati is a goddess who symbolizes art, knowledge, and spirituality in Hinduism. To realize a library as mentioned above, the Meaning of the Attribute Symbol of Dewi Saraswati can be a driving force to realize the tasks and functions of the library in the future, namely: (1) Beautiful Woman is a symbol of beautiful, attractive, gentle and noble power (2) Genitri is a symbol of immortality and unlimited knowledge (3) The Holy Library/Lontar is a symbol of the most sacred knowledge (4) The lotus is a symbol of the holiness of Ida Sang Hyang Widhi Wasa/God Almighty (5) The lotus is a symbol of the holiness of Ida Sang Hyang Widhi Wasa/God Almighty (6) The swan is a symbol of wisdom (7) A musical instrument, a symbol of high culture